Kepemimpinan Laki- Laki dan Perempuan dalam Islam - Anshori Anshori (Buletin Al-Turas, 2006)
The leadership question of male and female in Islam often becomes controversial. it could not happened when Muslims understand the text of Al-Qur'an and Hadis comprehensively, Husband can be a leader in his family becuse of his responsibilty in searching family needs (life cost). The leadership in society is not dtermined by gender or sex but byquality.